Akta wizytacyjne w strukturze zasobów historycznych archiwów diecezjalnych w Polsce - Dębowska, Maria (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The following paper suggests that the visitation records of churches and parishes from the Old Polish period be held in the structure of the fonds of diocesan historical archives (storing). This issue is omitted both in theory and practice of diocesan archives in Poland due to difficulties (or, as many claim-impossibility) in applying the principle of provenance to the production of the episcopal chancery during the period of functioning the book of inscriptions. So far, only the Rev. Stanisław Librowski has suggested the project to solve this problem. This project, however, does not fully respect, acknowledged in the archival science, the principle of provenance.